Ecstatic Antibodies: Art, Activism, and HIV/AIDS in "British" Art History - Theo Gordon (British Art Studies, 2025)
Opening at Impressions Gallery of Photography in January 1990, the exhibition *Ecstatic Antibodies: Resisting the AIDS Mythology*, curated by Tessa Boffin and Sunil Gupta, was a landmark effort to use artistic practices to intervene in the politics of representation of AIDS in the United Kingdom. While *Ecstatic Antibodies* has since faded from art-historical memory, this article resists the effort to recuperate it into a "canon" of "AIDS art", reading instead its archival fragments as testifying to the contingent nature of artistic responses to the political crisis of HIV/AIDS in Britain. By charting the development of the exhibition out of the problem space of the late 1980s, its controversial censorship, and the politics of vision and reproduction informing much of the work contained within it, the article contends that the form and fate of *Ecstatic Antibodies* offers new ways to conceive the history of art and HIV in Britain, and to reconceptualise gay, lesbian, and Black coalition building just prior to the provisional reclamation of the term "queer" in sexual and cultural politics.